BAHASA ARAB DAN METODE PENGAJARANNYA - Ana Achoita (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
Arabic is one language that has touched various world realms. Along with the development of the age, requires us to always move to follow it so that the method of learning arabic and its innovation will be a challenge. All methods are good, but the choice of a method is determined by many factors, including: teaching goals, background, student language, student age, available time, teacher readiness, and sociocultural factors.